Comparative analysis of ocular surface tissue microbiome in human, mouse, rabbit, and guinea pig. (June 2021) - Ozkan, Jerome; Majzoub, Marwan E.; Coroneo, Minas; Thomas, Torsten; Willcox, Mark
Abstract: Animal models are a critical element of ocular surface research for investigating therapeutic drops, surgical implants, and infection research. This study was a comparative analysis of the microbial communities on conjunctival tissue samples from humans compared to several commonly used laboratory animals (BALB/c mice, New Zealand white rabbits and IMVS colored stock guinea pigs). Microbial communities were analyzed by extracting total DNA from conjunctival tissue and sequencing the 16 S rRNA gene using the Illumina MiSeq platform. Sequences were quality filtered using the UNOISE pipeline in USEARCH and taxonomically classified using GTDB database. Sequences associated with blank extraction and sampling negative controls were removed with the decontam R software package prior to downstream analysis. There was a difference in the diversity measures of richness (P = 0.0124) and Shannon index (P = 0.0002) between humans and rabbits but not between human, mouse and guinea pigs. There was a difference between the human and any animal for bacterial community structure (P = 0.006). There was a higher degree of similarity between the bacterial composition of the human and mouse samples with each dominated by the phyla Proteobacteria and Firmicutes. The use of mouse models may be more appropriate for studies investigating changes to the ocular microbiome due to interventions such as application of antibiotics due to greater similarities in bacterial community structure and composition to humans. Highlights: An animal model with a similar microbial community composition would be beneficial for conducting interventional studies. 16 S rRNA gene sequencing was conducted to identify the microbial communities present on conjunctival samples from human, mouse, rabbit, and guinea pig. Although humans were different to the animals, the microbial composition and structure of the mouse more closely resembled humans.